PENGARUH MODEL PEMBELAJARAN ADVANCE ORGANIZER (AO) BERBATUAN MODUL DESAIN DIDAKTIS TERHADAP PEMAHAMAN KONSEP MATEMATIS - Clara Octaviany; Rizki Wahyu Yunian Putra; Istihana Istihana (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2019)
This research aims to determine the effect of the Advance Organizer learning model towards understanding the assisted mathematical concepts of didactic design modules in straight line equations of grade VIII SMP. The type of this research is a quasi-experimental design with